Mapping sustainability transitions : networks of innovators, techno-economic competences and political discourses /: networks of innovators, techno-economic competences and political discourses. (2016) - Marletto, Gerardo, 1961-; Franceschini, Simone; Ortolani, Chiara; Sillig, Cécile
No abstract available